Classifying UKT Fee Relief Eligibility Using K Nearest Neighbors Algorithm - Anggara Putra, I Wayan Kintara; Agastyar Priatdana, Gde Yoga (INFOTEKS (Information Technology, Computer and Sciences), 2023)
This research develops a K-Nearest Neighbors (KNN)-based classification model to determine the eligibility of students for Tuition Assistance (UKT) based on socio-economic factors, including parental income, family size, parental occupation, number of dependents, and housing conditions. The goal is to automate the process of identifying students eligible for financial aid, enhancing both the efficiency and fairness in resource allocation. The model was trained using a dataset consisting of both categorical and numerical features, with the target variable being binary: